Infecciones De Piel Y Partes Blandas En Pacientes Internados En El Servicio De Cl#xED;nica M#xE9;dica Del Hospital General De Luque En Los Meses De Marzo 2017 A Agosto 2017 (Global Journal of Medical Research, 2020)
Introduction: Currently, the skin and soft tissues infection are an important cause of consultation and even admition wide world. They have different presentations, etiology and severity. Therefore, it is a challenge to recognize the immediate needs for care and intervention, either medical or surgical, from less severe threats. Objective: To identify the most frequent skin and soft tissue infections in patients admitted to the Clinical Medical Service of General Hospital of Luque in the months of March 2017 to August 2017.
Keywords: infection of skin; soft tissues; cellulitis; diabetic foot